Dialog antara Nabi Sulaiman dengan Semut dalam Surah An-Naml (Analisis Makna Kontekstual) - Surianti; Halim, Abdul; Hamsa (Al-Syamail: Jurnal Bahasa dan Sastra Arab, 2024)
This thesis discusses the Dialogue between Prophet Solomon and Ants in Surah An-Naml (Study of Contextual Meaning). The core of this discussion is about Dialogue and Analysis of Contextual Meaning, with the formulation of the problem as follows: Forms of dialogue and forms of contextual meaning in the dialogue of Prophet Solomon with ants in the Qur'an. This research is qualitative researchdescriptive. This means that this research examines and describes the dialogue between the Prophet Solomon and ants in the Koran, especially regarding the dialogue format and contextual meaning. The approach used by researchers is a linguistic-semantic approach by analyzing the problems to be studied. The data collection technique is carried out through documentation by searching library research data to obtain scientific information collected through literature review as a reference for problems deemed appropriate, namely by searching for data related to the researcher's title. In analyzing data, researchers used qualitative methods. The results of this research show that of the many dialogues in the Koran, the dialogue of the Prophet Solomon is the most unique. Because he was one of the Prophets who was given the privilege of being able to speak directly with other creatures. In research that researchers examined in the Qur'an, researchers found elements of dialogue in surah an-Naml verses 17-19, namely; prologue, monologue, dialogue. There are 3 forms of dialogue, including; 1.) Indirect dialogue between Prophet Solomon and Allah, 2.) Direct dialogue between ants and fellow ants and 3.) Indirect dialogue between Prophet Solomon and ants. Meanwhile, the form of contextual meaning in verse 18 has 3 contextual changes, while in verse 19 there are 2 contextual changes